Aesthetics and ideology: communicational perspectives - Casallo, Víctor (2017)
The “ideology” notion has been decontextualized from its critical function to be employed as a discrediting maneuver that disregards debate. This article posits ideological analysis within the basic idea of a critical theory to point out the problems inherent to its dependency to the modern subjectivity paradigm. Afterdiscussing two attempts to preserve some form of ideological analysis by means ofa reconsideration of the aesthetical, we claim the pertinence of a communicationalinterpretation of the critic, ideology and aesthetics notions, which refers them to its founding and normative dimension in the very constitution of the self and its community.